The Contribution of Family and Community Education in Realizing the Goals of School Education - Maunah, Binti (American Journal of Education and Learning, 2019)
The role of family education, school and society is needed to achieve the success of students. Not without reason, the development and influence of the environment today will affect the child’s developmental body indirectly will have an impact on his future later. Children are a source of great potential for the continuity and progress of the nation. Literature studies conducted aim to provide an understanding of the importance of the role of partnerships in family education, schools and communities to shape the character of the nation’s children and explain how the process must be carried out to achieve these goals. The results of the study reveal that First, family environment, and the community environment has a very big role in supporting the achievement of educational programs in schools. Educational programs in schools cannot be achieved if they are not fully supported by families and communities. Second, the role of families in the process of achieving educational goals in schools can be seen from their participation in assisting and motivating children in learning, including in terms of financial support.Third, community participation in supporting the achievement of school goals can be realized in the form of participation in carrying out community learning hours, maintaining school safety, supporting various school programs that are directly in contact with the community.